Literature Review: Peran Suami Dalam Mendukung Pengoptimalan Pemberian Asi Eksklusif - Tyas Ratna Manggali; Diansanto Prayoga (Riviera Publishing, 2025)
Based on data from the World Health Organization (WHO) in 2021, only about 41% of babies aged 0–6 months in the world receive exclusive breast milk, a figure that is still far from the global target. In Indonesia, the low coverage of exclusive breastfeeding is influenced by various factors, including limited knowledge and awareness of health workers, the role of mothers as career women, and the lack of optimal support from the immediate environment, especially husbands and families. This study aims to examine the role of husbands in supporting the optimization of exclusive breastfeeding for breastfeeding mothers. The research method used is literature review by examining relevant scientific articles from the ResearchGate, ScitePress, and PubMed databases. The results of the study show that husband support has a significant role in the success of exclusive breastfeeding, which includes emotional support in the form of empathy and motivation, instrumental support such as helping with household chores, informational support through understanding the benefits of breastfeeding, and reward support that increases maternal confidence. Although most husbands have the awareness to support breastfeeding mothers, the level of knowledge about the proper form and method of providing support is still limited. Therefore, this study recommends the need for structured education and training for husbands as part of health promotive interventions to improve the success of exclusive breastfeeding and the degree of health of mothers and babies in a sustainable manner.